Country guesthouse - Carr, Robyn (Waterville, Maine Wheeler Publishing, a part of Gale, a Cengage Company, 2020)
After her best friend dies, Hannah Russell becomes the guardian of five-year-old Noah. Realizing they need time to get to know each other, Hannah rents a country house in rural Colorado. The home's handsome owner, Owen Abrams, promises to stay out of their way, but that plan is upended after Noah bonds with his dog. While Hannah learns to be a mother, Owen, who is also grieving, is drawn out of his solitude by his guests. But as life throws more challenges at this unlikely trio, they discover their strengths and fight to become a family. And the people of Sullivan's Crossing rally around them, offering all of their support.
107684
Keywords: Mothers and sons -- Fiction; Man-woman relationships; Rental housing; Grief; Colorado; Large type books; Domestic fiction; Romance fiction